Fulfilling Obligations and Rights During Covid-19 Pandemic: Policy Analysts Perspective - Ona Martha Nurron (Wacana Journal of Social and Humanity Studies, 2021)
AbstractThere was never a prediction of a pandemic occurred in 2020 transpired for nine months even more. It was a disruptive situation throughout the world, interfering every aspects and components of society. Although there is a popular opinion that civil servants are among the untouched occupations, some were struggling in the crisis. A relatively new profession in Indonesia Institute of Sciences is Policy Analyst, which demands a dynamic strategy to fulfill the obligations and rights of the jobs.Utilizing qualitative descriptive methods, this research aims to determine how far the covid19 pandemic affects the fulfillment of a policy analyst. Primary data extracted from interview along with secondary data from comprehensive literature were employed.The interesting findings were all-women policy analysts stationed in Bandung Campus of Indonesia Institute of Sciences are able to fulfill the obligations and rights while balancing between office and family life through the pandemic by coping strategy of collaboration and innovation.